Mass transfer and tidally tilted pulsation in the Algol-type system TZ Dra. Issue 1 (4th December 2021) - Kahraman Aliçavuş, F; Handler, G; Aliçavuş, F; De Cat, P; Bedding, T R; Lampens, P; Ekinci, Ö; Gümüș, D; Leone, F
ABSTRACT: Oscillating eclipsing Algols (oEAs) are remarkable systems that allow us to determine accurate fundamental stellar parameters (mass, radius) and probe the stellar interiors through pulsations. TZ Dra is an oEA system containing a δ Scuti component. To examine particular characteristics of such close systems including pulsations and mass transfer, we present a detailed photometric and spectroscopic study of TZ Dra. With the analysis of high-resolution spectra, the orbital parameters were determined by the radial velocity analysis and the atmospheric parameters were derived for the primary component. The binary modelling and the pulsational frequency analysis was carried out using the Transiting Exoplanet Survey Satellite data set. The H α line profiles show the signature of mass transfer from the cool to the hot binary component. The conclusion of mass transfer/mass-loss in the system was supported by the analysis of the orbital period changes. As a result, it was found that there is 3.52 × 10^-9 M_ yr −1 mass-loss from the system most probably through the hotspot and stellar winds. Additionally, most pulsation frequencies originating from the primary component were found to be spaced by harmonics of the orbital frequencies in particular, 12 doublets spaced by 2 f orb were detected from which we infer that this star is a tidally tilted pulsator. A mean p-mode frequency spacing of ≈7.2 d −1 was found as well.